Evaluation of Village Fund Management Policy in Poverty Alleviation in Majalengka Regency - Aay Kandar Nurdiansyah; Nandang Alamsah Deliarnoor; Novie Indrawati Sagita; Risma Pitriani Nuryana (Research Horizon, 2026)
This study is motivated by the critical role of village funds in enhancing community welfare and alleviating poverty in Indonesia. The study aims to evaluate the effectiveness of village fund management in poverty alleviation efforts in Majalengka Regency using policy evaluation criteria. Employing a qualitative research approach with a descriptive design, data were collected through in-depth interviews, observations, and documentation involving village government officials, village institutions, and community members. Data analysis was conducted using William Dunn’s policy evaluation framework, which encompasses six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that the management of village funds has generally been effective, with programs such as infrastructure development, direct cash assistance, food security initiatives, community empowerment, and the development of village-owned enterprises contributing to improved welfare and poverty reduction. The criteria of effectiveness, efficiency, adequacy, responsiveness, and appropriateness were assessed as satisfactory, whereas equity requires further attention due to the uneven distribution of benefits. The study highlights the need for more equitable distribution and inclusive community participation to strengthen the long-term impact of village funds, ensuring that their management is sustainable and fosters inclusive local development.